Possible role of eclosion rhythm in mediating the effects of light-dark environments on pre-adult development in Drosophila melanogaster - Paranjpe, Dhanashree A (BioMed Central, 2005)
BACKGROUND: In insects, circadian clocks have been implicated in affecting life history traits such as pre-adult development time and adult lifespan. Studies on the period (per) mutants of Drosophila melanogaster, and laboratory-selected lines of Bactrocera cucurbitae suggested a close link between circadian clocks and development time. There is a possibility of clock genes having pleiotropic effects on clock period and pre-adult development time. In order to avoid such pleiotropic effects we have used wild type flies of same genotype under environments of different periodicities, which phenotypically either speeded up or slowed down the eclosion clock of D. melanogaster. RESULTS: We assayed pre-adult development time and pre-adult survivorship of four laboratory populations of D. melanogaster, under five different light regimes, continuous light (LL), continuous darkness (DD), and light-dark (LD) cycles of 10:10 h (T20), 12:12 h (T24), and 14:14 h (T28). Although the development time was significantly different in most light regimes, except for females under T24 &T28, pre-adult survivorship remained largely unaffected. The development time was shortest under LL, followed by T20, DD, T24 and T28 regimes, in that order. Interestingly the development time showed a positive correlation with the period of eclosion rhythm, i.e., faster oscillations were associated with faster development, and slower oscillations with slower development. CONCLUSION: Based on these results we conclude that periodicity of imposed LD cycles, and/or of eclosion rhythm plays a key role in regulating the duration of pre-adult development in D. melanogaster in a manner that does not involve direct pleiotropic effects of clock genes on both clock period and development time.